Does Capital Structure Adjustment Improve Bank Profitability? Evidence from Dynamic Panel Models of Indonesian State-Owned Banks - Ahmad Fajar Ramadhan; Felix Fisabilillah Bayu; Wisnu Wibowo (University Merdeka Malang, 2026)
This study examines the effect of capital restructuring on the profitability of Indonesian state-owned banks. Profitability is measured using Return on Assets (ROA), while capital restructuring is represented by the Debt-to-Equity Ratio (DER) and Capital Adequacy Ratio (CAR). Non-performing loans (NPL) and operating expenses to operating income (BOPO) are included as control variables. The study uses panel data from four Indonesian state-owned banks—Bank Rakyat Indonesia, Bank Negara Indonesia, Bank Tabungan Negara, and Bank Mandiri—over the period 2019–2023. The analysis employs both static and dynamic panel regression methods, including Pooled Least Squares (PLS), Fixed Effects Model (FEM), Random Effects Model (REM), Difference GMM, and System GMM. The results indicate that operational efficiency, represented by BOPO, consistently has a negative and significant effect on bank profitability. The System GMM estimation suggests that capital restructuring variables significantly influence profitability. These findings highlight the importance of efficient cost management and sound capital structure policies in improving the financial performance of state-owned banks.